2018
DOI: 10.3389/fmicb.2018.01578
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a New Recombinant Vector to Remove Sulfate Repression of dsz Promoter Transcription in Biodesulfurization of Dibenzothiophene

Abstract: Biodesulfurization (BDS) is an environmentally friendly desulfurizing process with the potential of replacing or adding to the current expensive technologies for sulfur removal from fossil fuels. The BDS, however, still suffers from low biocatalyst activity. One reason is repression of dsz promoter transcription in presence of inorganic sulfate that impedes translation of Dsz enzymes required for desulfurization pathway. One approach to solve this problem is replacing the native promoter with a new promoter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Finally, HBPS is hydrolyzed into 2-hydroxybiphenyl (HBP) and sulphite by the DszB enzyme [84]. Increased BDS activity can be enhanced by recombinant strains through the manipulation of the Dsz gene [85]. For example, Raheb and Hajipour [86] used an engineered biodesulphurisation biocatalyst ( Pseudomonas aeruginosa ATCC 9027) for the BDS reaction.…”
Section: Application Of Biosurfactants In the Petroleum Industrymentioning
confidence: 99%
“…Finally, HBPS is hydrolyzed into 2-hydroxybiphenyl (HBP) and sulphite by the DszB enzyme [84]. Increased BDS activity can be enhanced by recombinant strains through the manipulation of the Dsz gene [85]. For example, Raheb and Hajipour [86] used an engineered biodesulphurisation biocatalyst ( Pseudomonas aeruginosa ATCC 9027) for the BDS reaction.…”
Section: Application Of Biosurfactants In the Petroleum Industrymentioning
confidence: 99%
“…At 1.1 mM and 2.6 mM DBT, almost-complete desulfurization was achieved (YBDS, 1mM= 96.7% and YBDS, 2.6 mM = 94%), while at the highest concentration (4.3 mM), approximately 76% of DBT was desulfurized (Figure 8). Khosravinia et al [42] reported that the biodesulfurization efficiency of Rhodococcus FUM94 resting cells decreased from 71.9% to 57.0% when DBT concentration changed from 0.13 to 0.54 mM, respectively. The specific DBT removal rate exhibited its highest value of 8.3 mm DBT/kg DCW/h at 1 mM initial DBT concentration, and remained almost constant after that.…”
Section: Effect Of Dbt Concentrationmentioning
confidence: 99%
“…In the specific biphasic system used, at 1.1 mM DBT, biodesulfurization was almost complete over a 6 h reaction time; at higher initial DBT concentrations, the time required to reach equilibrium increased with the increase in the amount of unreacted DBT. Khosravinia et al [42] reported that the biodesulfurization efficiency of Rhodococcus FUM94 resting cells decreased from 71.9% to 57.0% when DBT concentration changed from 0.13 to 0.54 mM, respectively. The specific DBT removal rate exhibited its highest value of 8.3 mm DBT/kg DCW/h at 1 mM initial DBT concentration, and remained almost constant after that.…”
Section: Effect Of Dbt Concentrationmentioning
confidence: 99%
“…Finally, the HBPS is hydrolysed into 2hydroxybiphenyl (HBP) and sulphite by the DszB enzyme [84]. Increased BDS activities can be enhanced by recombinant strains through the manipulation of a Dsz gene [85]. For example, Raheb and Hajipour [86] used an engineered biodesulphurisation biocatalyst (Pseudomonas aeruginosa ATCC 9027) for BDS reaction.…”
Section: Biosurfactants In Biodesulphurizationmentioning
confidence: 99%